The finance–inequality nexus in the era of financialisation: Evidence for Portugal - Barradas, Ricardo (2022)
Since the 1980s, Portuguese policy makers have engaged in a strong process of liberalisation, deregulation and privatisation of the financial system to adhere to the rules imposed by the European Economic Community and to promote financial growth, boost economic growth and reduce inequality. However, the Portuguese economic growth has exhibited a weaker performance and inequality has continued to widen in the last decades, a situation that seems to contradict the mainstream beliefs regarding the supportive role played by financial growth in the era of financialisation. This paper undertakes an empirical assessment of the finance–inequality nexus by performing a time series econometric analysis for Portugal from 1980 to 2020 through the estimation of both linear and non-linear models. It finds strong evidence for a positive (linear) relationship between finance and inequality and some evidence for a convex quadratic (non-linear) relationship between finance and inequality in Portugal, corroborating the hypothesis that the financial growth has been prejudicial, enhancing inequality in Portugal. These findings highlight the urgent need to abandon the so-called ‘trickle-down theory’ or the ‘horse and sparrow theory’ and to implement the so-called ‘trickle-up theory’ with the support of pro-poor public policies to decrease inequality in Portugal.